Medición del calor latente de vaporización del nitrógeno líquido en la enseñanza de la física experimental - Espitia R, Miguel J.; Báez C, Ricardo E.; Díaz F, Jhon H. (Revista Científica, 2011)
﻿Among the methods for teaching physics, one of the more instructive is the experiment, we presents a simple and inexpensive for the indirect measurement of the latent heat of vaporization of liquid nitrogen using typical elements of a general physics laboratory, such as resistors, voltage sources, multimeters, timers and a balance, with the latter measures the mass change in a container of liquid nitrogen with respect to the time, when the nitrogen is heated with a resistance when it passes by an electric current, we found a proportionality between the electric power supplied to nitrogen, time and the mass of Nitrogen evaporated, which relate to the latent heat of vaporization of nitrogen.